Psychosocial findings in alcohol-dependent patients before and after three months of total alcohol abstinence - Ferrulli, Anna; Leggio, Lorenzo; Cardone, Silvia; D'Angelo, Cristina; Mirijello, Antonio; Vonghia, Luisa; Miceli, Antonio; Gasbarrini, Giovanni; Addolorato, Giovanni (Frontiers in Psychiatry, 2010)
Alcohol use disorders (AUDs) may be associated with several psychological and affective disorders. It is controversial, however, if these symptoms are a cause or rather a consequence of alcohol dependence. There are few data testing simultaneously psychosocial and affective disorders before and after a period of alcohol abstinence. The aim of this study was to perform multiple psychometric evaluations in alcohol-dependent patients before and after 12 weeks of abstinence. Twenty-five alcohol-dependent patients were included in the study. The following psychometric tests were administered at baseline (T0) and after 12 weeks (T1): Addiction Severity Index (ASI), Brief Psychiatric Rating Scale (BPRS), Social Behaviour Scale (SBS), Sheehan Disability Scale (DISS), Aggression Questionnaire (AQ). At T1, 16 (64%) patients were abstinent, 5 (20%) patients dropped out and 4 (16%) patients relapsed. Compared to T0, patients totally abstinent at T1 showed a significant reduction of the scores related to BPRS, BPRS-E and its subscales (except BPRS 5), ASI 1, ASI 2, ASI 3, ASI 6, ASI 7, BSM, AQ, DISS 1, DISS 2, DISS 3 (p<0.05). No significant changes in ASI 4, ASI 5, DISS 4 and DISS 5, BPRS 5 scores were found at T1 compared to T0. The present study indicates that total alcohol abstinence improves psychometric features, such as alcohol addiction severity, psychiatric rating, social behaviour, aggressiveness, and disability. Larger controlled studies are needed to confirm these findings.